1785 Del. Acts. May Adjourned Sess. 11-13 - (:unkn) unknown (My University, 1785)
Each white male 18-50 whose taxes were at least twenty shillings a year had to provide equipment " at his own expence." As for apprentices and persons over 18 and under 21, their parent or guardian would provide the arms" if the militiaman" s estate were at least eighty pounds, or if the parent paid " six pounds annually towards the public taxes." Arms were " a musket or firelock, with a bayonet," a cartridge box with twenty-three cartridges, " a priming wire, a brush and six flints, all in good order." Fines for neglect were to be paid by militiamen " of full age or by the parent or guardian of such as are under twenty-one years." The guardian could charge his ward for the expense when the time came for " settling the accounts of his guardianship."
Keywords: MILITIAS; REQUIRED POSSESSION